(untitled) (Progressive Agriculture, 2017)
Mechanical rice transplanting is gaining attention to the Bangladeshi farmers. However, service business on mechanical rice seedlings transplanting has not yet been developed due to various reasons. The 4-row walking type transplanter (model DP488) was operated in 54 farmer’s field at Ghaghatpara, Rangpur Sadar and Kaliganjpara, Pairaband, Rangpur in late boro 2016 season to explore the entrepreneurial opportunity of commercial mechanical rice transplanting service for small holder farmer in Bangladesh. The field capacity and field efficiency of rice transplanter was obtained 0.15 ha hr-1 and 75%, respectively. Field capacity depended on the size and shape of the plots. Small plots having less than 250 m2 should be avoided for 4-row walking type rice transplanter to get the good machine performance. Fuel consumption was obtained 4 L ha-1 and varied over plot size, soil settlement time, presence of obstacle, plot to plot travelling distance and operator’s skill. Scattered plots increased travelling distance hence fuel consumption raised and reduced daily area coverage. Soil setting time should be allowed for 12-24 hrs for satisfactory machine performance. Mechanical transplanting took 18 man-hr ha-1 whereas mat loading, machine transport and cleaning took 1.6 man-hr ha-1 labors. Depending on the combination of seedling density in tray and density settings in machine the tray requirement varies from 153 ha-1to 222 ha-1. Tray distribution was observed as 90% in transplanting, 6% in gap filling and 4% pocket area. Gap filling by manual labor required 18-20 man-hr ha-1. Time distribution depended on managerial combination and relation between transplanting team and farmers. Seed rate showed negative correlation with seedlings population in tray and positive correlation with seedlings mortality. Number of turning events in plots can be minimized by selecting larger plot and operating transplanter in length-wise. Increasing daily coverage, minimizing fuel consumption and selection of sensible consumer group can draw good return from marginal input and establish business in secure environment. Progressive Agriculture 28 (3): 230-239, 2017